Revealing Consumer Motivation on The Shopee Marketplace Toward Natural-Based Skincare Products - Muslimah, Tsaniatu; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The rapid developments in Indonesian cosmetic industry have brought various choices of skincare products for customers. Therefore, they need to be more selective in choosing the suitable products. Natural-based skincare products offer natural ingredients safer for the skin and the environment. However, consumers’ motivations for choosing certain products are subjective since they depend on their individual assessments and interpretations. Therefore, understanding consumer motivation, being difficult and complex, is not an easy task. The objective of this qualitative case study is to analyze elements that can motivate consumers to choose natural-based skincare products. The research subject consists of five informants who have purchased the natural soap products of Aurolia.id via Shopee. The data was harvested through interviews, document studies, and library research, by which elaborate findings were acquired. This study finds that the factors that motivate consumers’ choice include prices that are more competitive than those of similar products, positive reviews from other consumers, relational proximity between them and the business owner, their knowledge about the products, the quality of the product, their proximity with the seller’s location, and distribution channels provided by Shopee.